SBY FRAMING IN TELEVISION NEWS INDONESIA - Amri Dunan (Puslitbang Literasi dan Profesi SDM Komunikasi dan Informatika, 2014)
Controversies news about the President Susilo Bambang Yudhoyono (SBY) becomes a contentious issue in the Indonesian media. This article describes and analyzes the framing of SBY verbally and nonverbally in the news of Metro TV and TV One during in 2013. This research uses framing analysis “Television News” model (Dunan & Adnan, 2013) and the inductive qualitative analysis with matrix method (Van Gorp, 2010). This study revealed three media perspectives are SBY as an individual, politician, and the president. News media broadcasting tend to bias and ambiguous when interprets SBY as the president who is also a politician or vice versa. Bias of SBY’s framing tends to be influenced political ideological basis of the television media owner. Keywords: media framing, President, television news, verbal and non verbal